RIOMETER RECORDS OF 30 MHz COSMIC NOISE AT SYOWA STATION, ANTARCTICA IN 1977 - OSE, Masami; NISHIYAMA, Noboru; SAKAMOTO, Junichi (National Institute of Polar Research, 1978)
P(論文) departmental bulletin paper